SISTEM PENDUKUNG KEPUTUSAN PEREKRUTAN KARYAWAN BERBASIS WEB MENGGUNAKAN METODE MOORA - Sanjaya, Irfan; Hajjah, Alyauma (Universitas Trunojoyo Madura, 2024)
PT. Sinar Indrapura Anugerah Khatulistiwa is a company that operates in the gas sales sector and hires 30 employees every year. Based on the results of the interview, this company agreed to use a decision support system to support the employee recruitment process to avoid subjective factors that are detrimental to job seekers and the company. The decision support system will be built using the MOORA method because this method has a simple and easy to understand concept and provides precise and accurate results to support decision making, is easy to implement and has a high level of sensitivity to the attributes used compared to other methods. The criteria that are considered appropriate are the criteria to support the employee recruitment decision support system at PT. Sinar Indrapura Anugerah Khatulistiwa is education level, age, work experience, health, written test scores and interview scores. This research is expected to be able to design and implement a web-based employee recruitment decision support system using the MOORA method. As a result, the system was successfully designed and implemented on a web basis using the MOORA method with the results of manual calculations matching the calculation results of the system with an accuracy level of 100% so that the system was declared suitable for use as a decision support system for employee recruitment and all of its functionality was running 100%.Keywords: Decision Support System, Employee Recruitment, MOORA Method, Web